Die Jakobpassagen in Hos 12 - Schott, Martin (Zeitschrift für Theologie und Kirche, 2015)
The enigmatic 12th chapter of Hosea neither bears witness to the state of development nor to the existence of a pre-priestly Jacob tradition in the 8th century BCE. The literary-historical core of the chapter can be found in the pre-deuteronomistic accusation and the announcement of judgment against the deceitful Ephraim. The references to Jacob are later additions which reflect on the moral and theological significance of the ancestor for contemporary Israel by drawing on the canonical Jacob narratives.
Keywords: Hosea; Jakob; Mose; Exodus